Actinic reticuloid: case report - E. V. Sokolovskiy (Vestnik Dermatologii i Venerologii, 2019)
This article is about the case of actinic reticuloid — the rare dermatosis which clinical presentation is similar to atopic dermatitis, T-cell lymphoma. Good treatment effect was obtained by long cycles (2 cycles for 3 months) of hydroxychloroquine and sun protective therapy included sunscreens SPF 50, nicotinic acid, sun-safe clothes which blocked ultraviolet radiation without any glucocorticosteroid drugs and cytostatic treatment.